Are employee assistance programs helpful? A look at the consequences of abusive supervision on employee affective organizational commitment and general health. Issue 4 (27th January 2022) - Wang, I-An; Lin, Hui-Ching; Lin, Szu-Yin; Chen, Pei-Chi
Abstract : Purpose: Abusive supervision has been a prevalent issue in the workplace. This study aims to explore the consequences of abusive supervision on employee affective organizational commitment and general health in the hospitality industry and further explores the boundary conditions of employee assistance programs (EAPs). Design/methodology/approach: The participants of this study were 231 frontline employees from the hospitality industry in Taiwan. Quantitative data was collected using questionnaires from two time periods separated by a two-week interval. The data was analyzed using PROCESS macro for SPSS. Findings: The findings from this study suggested that abusive supervision have negative impacts on both subordinates' affective organizational commitment and general health. As expected, perceived effectiveness of EAPs moderated the relationship between perceived abusive supervision and affective organizational commitment, whereas the moderating effect of perceived effectiveness of EAPs on the relationship between abusive supervision and employee general health was not significant. Practical implications: The results of this study showed that EAP practices can mitigate the negative effects of abusive supervision. It is expected to encourage managers in the hospitality industry to minimize or even prevent abusive supervision. Further, the authors suggest organizations implement specific strategies in their EAPs to assist employees in coping with the negative emotions accompanying abusive supervision. Originality/value: This study offers empirical evidence that illustrates the importance of EAPs and how they may reduce the negative impacts of abusive supervision.